ISLAH AS THE KEY SUCCESS OF TERRORIST DISENGAGEMENT PROCESS IN INDONESIA - Priyanto, Sapto; Dermawan, Mohammad Kemal; Runturambi, Arthur Josias Simon (Journal of Al-Tamaddun, 2020)
This study describes about the process of disengagement from terrorist in Indonesia using the Islah, one of the methods of Islamic characters. Islah is a method to make a gathering between terrorism victims, terrorist in prison and their networks in order to build a bridge of communication within them. The activities of Islah consist of various forms such as, gatherings, gathering with nationalism insight or focus group discussions and build the individual friendship. The sincerity of the terrorism bomb victims who had forgiven the terrorist before the meeting made the former convicts of terrorism cases feel guilty and their heart is touched. They cried and apologized for the actions of his friends and what they had done. Islah make the reconciliation between the victims and the terrorist happened naturally. The finding of this study shows that Islah as a method of reconciliation can be applied in Indonesia. Most participants feel sympathized and apologized to the victims. The friendliness of the facilitator and stakeholders makes Islah more effective to do. Islah is one of effective reconciliation method with the right note in selecting sources from terrorism victims and participants from former convicted terrorism cases and their networks in the Indonesian context, but Islah is not easy to do for perpetrators from Poso, Central Sulawesi and Ambon, because they also consider themselves as the victims. Islah is one of the local wisdoms of the Indonesian people and was founded since the Kingdom of Majapahit era. Islah as one of Islamic character of Islam is the key to the success of disengagement in Indonesia